Baduanjin’s impact on quality of life and sleep quality in breast cancer survivors receiving aromatase inhibitor therapy: a randomized controlled trial - Liao, Jingwen; Chen, Yanyu; Cai, Li; Wang, Kun; Wu, Shenghui; Wu, Lan; Song, Bixiao; Hu, Min; Hou, Xiaohui (Frontiers in Oncology, 2022)
Purpose The aim of the current study is to investigate the impact of Baduanjin, a traditional Chinese exercise, on quality of life and sleep quality in breast cancer survivors receiving aromatase inhibitor (AI) therapy. Methods A total of 72 breast cancer survivors who had received AI treatment for more3 than 6 months were enrolled in the current study using non-probability consecutive sampling procedure. Participants were randomly assigned in a 1:1 ratio to a 12-week Baduanjin exercise program or to a wait-list control group. The Baduanjin exercise group performed two 90-min supervised sessions per week. The primary outcomes were changes in quality of life measured by the European Organization for Research and Treatment of Cancer Quality-of-Life Questionnaire Core 30 (EORTC QLQ-C30) and in sleep quality evaluated using the Pittsburgh Sleep Quality Index (PSQI). Results A total of 68 participants completed the trial (Baduanjin exercise group: n = 33; control group: n = 35). Baseline values for quality of life did not differ between groups. Both global quality of life and physical functioning scores increased significantly by 12.39 (P < 0.001) and 8.48 (P < 0.001) in the Baduanjin exercise group compared with those in the control. Overall PSQI score also decreased by 4.85 (P < 0.001) in the Baduanjin exercise group, whereas it increased by 0.34 in the control group. Conclusion Baduanjin exercise training led to improvement in the quality of life and sleep quality of breast cancer patients undergoing AI therapy.